Unveiling the Shadow of Workplace Cyberbullying in the Digital Age: A Call for Research in Africa - Cheryl Akinyi Genga; Sunday Samson Babalola (Businesses)
Workplace cyberbullying, exacerbated by the growing prevalence of digital work environments, has emerged as a significant threat to employee well-being and organisational productivity. Despite increasing research attention around the world, there is a critical gap in understanding the unique context and implications of cyberbullying within African workplaces, particularly those operating in digital spaces. This bibliometric analysis, utilising Scopus and Web of Science databases, systematically examines the publications on workplace cyberbullying from 2000 to 2024 using Microsoft Excel and visualisation tools such as VOS Viewer. The findings underscore a stark disparity in research focus, with most studies originating from developed countries and neglecting African organisations’ specific challenges. Although South Africa and Ghana have made initial contributions, a comprehensive understanding of the prevalence, manifestations, and consequences of cyberbullying in diverse African cultural and organisational settings in Africa remains elusive. This study serves as a call to action for researchers and practitioners to prioritise investigations into cyberbullying in Africa, highlighting the need for culturally sensitive interventions and policies tailored to digital work environments. By addressing this research gap, organisations can promote healthier and more sustainable workplaces for employees across Africa.